Islamic Education Policy in Indonesia (Lembaga Pengembangan Kinerja Dosen, 2024)
The integration of Islamic education into a nation’s educational system represents a strategic effort to align religious and national educational objectives under a unified policy framework. In many Muslim-majority countries, the responsibility for managing Islamic education is delegated to local governments as part of a broader national consensus involving various educational stakeholders. This arrangement, however, often raises tensions because education policy is inherently a political decision influenced by state interests and ideological considerations. The process of incorporating Islamic education within the national system reflects the dynamic interplay between religion and politics, where Islamic education both shapes and is shaped by political structures. This study explores how political power affects the development, autonomy, and implementation of Islamic education policies. The objective is to highlight the challenges of maintaining educational freedom and religious authenticity while ensuring state oversight and quality assurance. The findings emphasize that a deep understanding of educational politics enables Muslim educators and policymakers to advocate for Islamic education that aligns with Islamic principles yet remains relevant within the national educational framework. Therefore, the balance between state control and institutional independence is essential in realizing the holistic goals of Islamic education in contemporary society.